PENINGKATAN KETERAMPILAN MENULIS NASKAH DRAMA MENGGUNAKAN MEDIA CERPEN - Nani Angraini; Rohana Rohana; Abdulloh Abdulloh (LPPM STKIP PGRI Bandar Lampung, 2021)
This study aims to determine the improvement of drama script writing skills using short stories media for class IX.4 students of SMP Negeri 13 Bandar Lampung in the 2020/2021 academic year. The problem that occurs in this study is the low ability of students in writing drama scripts. This is caused by the lack of student interest in participating in learning and the lack of teacher creativity when using learning media that is easy and fun, so that students have difficulty participating in learning to write drama scripts. The data collection method used is the observation method, the test method (in the form of an assignment to write a play script), and the documentation method. The data collected were analyzed using qualitative and quantitative data analysis. The implementation of this research consisted of two cycles, namely cycle I and cycle II. Based on the results of the learning process, the use of short stories media can improve the quality of the process and learning outcomes of writing drama scripts for class IX.4 students of SMP Negeri 13 Bandar Lampung in the 2020/2021 academic year.